Morphometric characteristics of Antarctic krill (Euphausia superba) and finfish bycatch in the krill fishery in the waters of South Orkney Islands during the 2022/23 fishing season - Wang, Zhongqiu; Ma, Shuo; Wang, Yongjin; Wang, Lumin (Frontiers in Marine Science, 2024)
Determination of bar spacing of bycatch reduction devices (BRDs) should consider species composition and morphometric characteristics (particularly width) of target species krill and bycatch. This study conducted a scientific investigation of the finfish bycatch in the Antarctic krill (Euphausia superba) trawl fishery by the fishing vessel SHEN LAN in the waters surrounding the South Orkney Islands from December 24, 2022, to February 20, 2023. The results show that scientific observers sampled 676 individuals of finfish bycatch. Of these, 665 were identified to species (17 species from 8 families), while the remaining 11 specimen were juveniles of the Nototheniidae family that could not be identified to the species level. IRI (index of relative importance) calculations showed three dominant (IRI value greater than 1,000) finfish bycatch species (Champsocephalus gunnari, Pseudochaenichthys georgianus, and C. aceratus from the Channichthyidae family) and four important (IRI value between 1,000 and 100) finfish bycatch species (Electrona carlsbergi and Gymnoscopelus nicholsi from the Myctophidae family, Gobionotothen gibberifrons from the Nototheniidae family, and Notolepis coatsi from the Paralepididae family). Our study provides morphometric data (particularly body width) that is crucial to model the potential for bycatch reduction by use of bycatch reduction devices (BRDs) and to determine the appropriate candidate bar spacings for BRD sea trials. Predictions suggest that a 10 mm (the maximum body width of krill) bar spacing releases a significant amount of dominant and important bycatch species (93.94% of C. gunnari, 53.99% of P. georgianus, 76.25% of C. aceratus, and 100% of G. gibberifrons). Reduced fishing pressure would reduce the risks to dominant and important bycatch species to make the krill fishery sustainable. We recommend that future BRD sea trials should initially test a 10 mm bar spacing. If marked loss of krill is observed, wider spacings (e.g. 15 mm) must be tested.